Place Names and Related Concepts Study - Bakhtiyorovna, Nodira Adizova (European Journal of Life Safety and Stability (2660-9630), 2022)
The thematic-nominal classification of Bukhara district toponymy is presented in this article. The names of some microtoponms include the names of the Turkic peoples, including the tribes and tribes of the Uzbek people, and their branches and networks, and we have analyzed and commented on them. It discusses topical issues of toponymics, including the etymology of microstructures of Bukhara district.